Analysis and implementation of hydroacoustic methods for estimation of high densities of fish in sea pens - STEPNOWSKI, A. (Archives of Acoustics, 1993)
The paper presents the feasibility study of different acoustic methods with reference to system design, capable of estimating high density of fish, e.g. in aquaculture facilities. The velocity, attenuation and backscattering measurement methods are critically examined. The new, recursive echo integration method is introduced, which accounts for attenuation loss by dense collections of fish. The proposed implementation of this estimation technique employs the modified design of a dual-beam sonar-system ECOLOG II. The system provides the real-time absolute estimates of fish density in sea pens.